2019
DOI: 10.34044/j.anres.2019.53.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of betulinic acid and antioxidant and anti-HIV-1 reverse transcriptase activity of Cratoxylum formosum subsp. pruniflorum (Kurz) Gogelein extract

Abstract: Cratoxylum formosum subsp. pruniflorum (Kurz) Gogelein has been used as a medicinal plant for the treatment of many diseases. C. formosum bark was macerated with methanol and partitioned using hexane and chloroform. The chloroform bark extract was fractionated using column chromatography. Five combined fractions were obtained (CFA-CFE) and then investigated for antioxidant activity based on the total phenolic content (TPC), total flavonoids content (TFC), ferric reducing antioxidant power (FRAP) and nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Crude methanol extract and five fractions (CFA, CFB, CFC, CFD, and CFE) obtained from crude chloroform extract were tested. One of the chloroform fractions, CFE, exhibited effective anti-HIV-1 reverse transcriptase activity, similar to the positive control, Nevirapine, while the rest of the samples showed low inhibition (Srisombat et al, 2019).…”
Section: Anti-hiv-1 Reverse Transcriptasementioning
confidence: 82%
“…Crude methanol extract and five fractions (CFA, CFB, CFC, CFD, and CFE) obtained from crude chloroform extract were tested. One of the chloroform fractions, CFE, exhibited effective anti-HIV-1 reverse transcriptase activity, similar to the positive control, Nevirapine, while the rest of the samples showed low inhibition (Srisombat et al, 2019).…”
Section: Anti-hiv-1 Reverse Transcriptasementioning
confidence: 82%
“…had a high relative inhibition against HIV-1 RT compared with nevirapine, an anti-HIV drug, as a positive control (Soun-udom et al, 2019). Srisombat et al (2019) reported the methanolic extract from the stem bark of Cratoxylum formosum subsp. pruniflorum (Kurz) Gogelein also had, at least a similarly high level of anti-HIV-1 RT activity as the standard drug.…”
Section: Introductionmentioning
confidence: 99%